2015
DOI: 10.1016/j.bbr.2014.09.001
|View full text |Cite
|
Sign up to set email alerts
|

The neural representation of 3-dimensional objects in rodent memory circuits

Abstract: Three-dimensional objects are common stimuli that rodents and other animals encounter in the natural world that contribute to the associations that are the hallmark of explicit memory. Thus, the use of 3-dimensional objects for investigating the circuits that support associative and episodic memories has a long history. In rodents, the neural representation of these types of stimuli is a polymodal process and lesion data suggest that the perirhinal cortex, an area of the medial temporal lobe that receives affe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 100 publications
(176 reference statements)
0
4
0
Order By: Relevance
“…Thus, the prior literature is most consistent with a role for the PRC in item processing, and the finding of a context similarity effect in the PRC was unexpected. However, there is some evidence that the PRC may additionally carry some information about context, such as the locations of items in space ( Burke and Barnes, 2014 ). PRC lesions have been shown to disrupt some forms of context memory, including object–context associations ( Norman and Eacott, 2005 ), positional changes in object arrays ( Norman and Eacott, 2005 ), and contextual fear ( Bucci et al, 2002 )—although these impairments have typically been more circumscribed than those observed following PHC damage ( Norman and Eacott, 2005 ).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the prior literature is most consistent with a role for the PRC in item processing, and the finding of a context similarity effect in the PRC was unexpected. However, there is some evidence that the PRC may additionally carry some information about context, such as the locations of items in space ( Burke and Barnes, 2014 ). PRC lesions have been shown to disrupt some forms of context memory, including object–context associations ( Norman and Eacott, 2005 ), positional changes in object arrays ( Norman and Eacott, 2005 ), and contextual fear ( Bucci et al, 2002 )—although these impairments have typically been more circumscribed than those observed following PHC damage ( Norman and Eacott, 2005 ).…”
Section: Discussionmentioning
confidence: 99%
“…Four other methodological issues may be discounted as reasons for the difference in findings. (i) In the paired viewing arena the stimuli were two‐dimensional, rather than three‐dimensional as in the object arena (Burke and Barnes, ). However, this difference is unlikely to be important as recognition‐related responsiveness has been found for 3‐D objects (Zhu and Brown, ; Zhu et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…While neural representation of stationary objects has been studied systematically in the hippocampus ( Gothard et al, 1996 ; Rivard et al, 2004 ), anterior cingulate cortex ( Weible et al, 2009 , 2012 ), perirhinal cortex ( Burke et al, 2012 ; Deshmukh et al, 2012 ; Burke and Barnes, 2015 ) and medial ( Høydal et al, 2019 ) and lateral entorhinal cortex ( Deshmukh and Knierim, 2011 ; Wang et al, 2018 ), the neuronal substrate for representations of moving objects were previously assessed in only a few studies. Earlier studies reported that hippocampal neurons responded to the position of moving objects in allocentric space but they rarely assessed the responses to position of a rat relative to moving objects (for such exception see Ho et al, 2008 ).…”
Section: Discussionmentioning
confidence: 99%